2018
DOI: 10.1007/s42452-018-0066-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for utilization of agro-industrial waste materials as reinforcement with Al–7Si–0.3Mg matrix hybrid composite on tribological behaviour

Abstract: Waste particles are the huge environmental problem facing today. This paper mainly focuses on utilization of waste particles and aspect of tribology by examining economic, environmental impact on wear loss and coefficient of friction. Aluminium with a different weight fraction of agro (RHA) and industrial (fly ash) waste particulates are fabricated by double stir-casting process. The dry sliding wear behaviour of Al alloy and aluminium hybrid composites for various applied load, sliding distance with sliding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The pore system can be divided into different porosity if treated as a connecting pore network and channels of small diameters. The experimental density was determined by the Archimedes principle [17]. According to the ASTM B962-13, Porosity (P) was calculated for all the mixtures using Eq.…”
Section: Porositymentioning
confidence: 99%
“…The pore system can be divided into different porosity if treated as a connecting pore network and channels of small diameters. The experimental density was determined by the Archimedes principle [17]. According to the ASTM B962-13, Porosity (P) was calculated for all the mixtures using Eq.…”
Section: Porositymentioning
confidence: 99%
“…Lakshmanan et al [7] examined the problems associated with attaining homogeneously distributed reinforcements and better wettability with minimum porosity in the casting process. Vinod et al [8] revealed that the fly ash particulates in the matrix using the squeeze casting method had more advantages than using the manufacturing process of gravity type casting. A homogenous structure with less porosity, excellent interfacial bonding, and uniform distribution between particles was obtained.…”
Section: Proceedings Of Engineering and Technologymentioning
confidence: 99%
“…The study majorly studied the tribological characteristics of the reinforcements in the Al–7Si-0.3Mg matrix. Vinod et al. (2019) Coconut shell ash (CCA) 44.1 14.6 13.4 0.67 17.2 0.42 - 0.35 0.22 Squeeze casting LM 24 alloy was reinforced with hybrid SiC and CSA reinforcements.…”
Section: Biomass Materials Utilization As Reinforcements In Metal Matrix Compositementioning
confidence: 99%